2015
DOI: 10.1166/jnn.2015.11217
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH and Salt on Adsorption of Double-Stranded DNA on Graphene Oxide

Abstract: Graphene oxide (GO) has a large surface-to-volume ratio and hydrophobic hexagonal rings that can interact with biomolecules. Single-stranded DNA adsorbs strongly to the surface of GO via hydrophobic interactions. GO has been used in optical biosensors and biomedical platforms for the detection of DNA, proteins, and small molecules. This study was designed to measure the adsorption of double-stranded DNA (dsDNA) onto GO according to DNA length, salt concentration, and pH of the reaction. Results showed that dsD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Overall, results in the presence of magnesium ions were more reproducible, consistent with the observations of Lei et al, that metallic ions, such as Mg 2+ , Ca 2+ , Na + and K + induced a good distribution of DNA macromolecules on the surface of graphene oxide and facilitated the formation of dsDNA/GO and/or ssDNA/GO complexes as metal ions neutralized the electrostatic repulsions between the macromolecule and the nanomaterials [ 30 ]. Moreover, our results confirmed that the presence of metallic ions facilitated the quenching of the dsDNA on GO and GO-COOH surfaces [ 47 ]. Double-helix formation induces a conformational length change of the joining single-stranded molecules.…”
Section: Discussionsupporting
confidence: 78%
“…Overall, results in the presence of magnesium ions were more reproducible, consistent with the observations of Lei et al, that metallic ions, such as Mg 2+ , Ca 2+ , Na + and K + induced a good distribution of DNA macromolecules on the surface of graphene oxide and facilitated the formation of dsDNA/GO and/or ssDNA/GO complexes as metal ions neutralized the electrostatic repulsions between the macromolecule and the nanomaterials [ 30 ]. Moreover, our results confirmed that the presence of metallic ions facilitated the quenching of the dsDNA on GO and GO-COOH surfaces [ 47 ]. Double-helix formation induces a conformational length change of the joining single-stranded molecules.…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, we explored the dynamic process of the adsorption of ssDNA and dsDNA on G d rGO-PEG-NH2 under the influence of Mg 2+ and Cl − ions to better understand their impa 2,13]. Notably, we confirmed that for GO, the addition of Mg 2+ ions critically contributed DNA adsorption and provided an atomistic perspective for the adsorption process.…”
Section: Generation Of the Dna Moleculesmentioning
confidence: 68%
“…The resulting charge repulsion lowers the binding affinity of the dsDNA to the negatively charged oxygen atoms on the GO surface. Both experimental and computational studies have investigated the different aspects regarding the effect of using nucleic acids and different graphenic molecules [9][10][11][12][13]. Experimental studies showed that both Mg 2+ ions and functionalized derivatives of graphene, in particular an aminated polyethylene glycol-functionalized reduced graphene oxide (rGO-PEG-NH 2 ), markedly influenced detection of DNA hybridization [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 By contrast, some surfactants, such as Tween 20 and Triton X-100, strongly interfere with the formation of dsDNA/GO complexes. 30,34 We deduced that the short primer-dimers (usually less than 40 bp) might be selectively adsorbed by GO from PCR products under a carefully optimized condition. As a result, this new test strip coupled with the on-strip GO purification should be able to overcome the troubles associated with the conventional antibody-based method without causing any inconvenience to the overall detection process.…”
mentioning
confidence: 99%